2021
DOI: 10.1097/bpo.0000000000001840
|View full text |Cite
|
Sign up to set email alerts
|

Formal Patient Complaints and Malpractice Events Against Pediatric Orthopaedic Surgeons

Abstract: Background: Formal patient complaints are associated with increased malpractice litigation and can have adverse occupational consequences for surgeons. Our purpose was to define and categorize patient complaints within an academic pediatric orthopaedic surgery practice over a 10-year period. We further aimed to define risk factors associated with patient complaints. Methods: We reviewed all complaints within our institution's patient advocacy service filed on behalf of a patient against 4 pediatric orthopaedic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…This compares to a 0.20% complaint rate among hand and upper extremity surgeons and a 0.15% complaint rate among pediatric orthopedic surgeons, which have been previously reported by our group. 6,8 These data are consistent with results from Dambrino et al, 9 who demonstrated that spine neurosurgeons had an increased risk of complaints compared with other physicians. Our overall malpractice event rate among the six surgeons was found to be 0.23%.…”
Section: E523supporting
confidence: 86%
See 3 more Smart Citations
“…This compares to a 0.20% complaint rate among hand and upper extremity surgeons and a 0.15% complaint rate among pediatric orthopedic surgeons, which have been previously reported by our group. 6,8 These data are consistent with results from Dambrino et al, 9 who demonstrated that spine neurosurgeons had an increased risk of complaints compared with other physicians. Our overall malpractice event rate among the six surgeons was found to be 0.23%.…”
Section: E523supporting
confidence: 86%
“…Interestingly, while prior series have shown the association between patient demographics (obesity, tobacco use, and worker’s compensation) and surgical complications, these were not associated with complaints in our series or prior similar studies of other orthopedic subspecialties. 6,8,16–18…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An injury or its treatment can negatively impact a patient's social encounters, mental health, and ability to work, thus lowering their quality of life [14][15][16][17]. Ji et al [18] concluded that up to 34.6% of all patients undergoing a maxillofacial procedure sustain at least minor permanent harm, with the rate of death being up to 5.3%.…”
Section: Discussionmentioning
confidence: 99%